Formação, produção de saberes e da identidade docente: desafios e possibilidades de redimensionamento das práticas pedagógicas - Silva, José Amarildo Alves da (2013)
This thesis discusses the process of training teachers for the early years of Elementary School and aims to analyze the process of training students in the Pedagogy Major and its contribution to knowledge production, the construction of identity in teaching and the resizing of pedagogical practices. In research conducted under the parameters of a qualitative boarding, the study involved the participation of ten (10) graduated students, already working as teachers of basic education in Pedagogy of Centro de Formação de Professores da Universidade Federal de Campina Grande e do Centro de Educação da Universidade Federal da Paraíba, in addition to the coordinators of the two majors. Data collection was performed by the procedures of using semi-structured interviews since this technique allows the interviewee help in the investigation process with freedom and spontaneity without losing objectivity. The analysis was done by comparing the information and / or supporting the speech of the subjects interviewed with the theoretical framework adopted. The techniques of content analysis, defined by Laurence Bardin, were used for the interviews. The results shown in the course of the analysis of the speeches investigation showed that the training process experienced in Pedagogy majors in CFP and CE allows the acquisition of diverse knowledge and professional skills development and abilities required for the teaching practice. However, it has gaps that need to be met in order to promote the construction of teacher identity and the redefinition of their educational practices. It also shows that, without ignoring the importance and necessity of a solid theoretical foundation of professional education, one can argue, that in addition, only a systematic reflection and continuous production processes/knowledge mobilization in interface with the concrete conditions of teaching work exercise, makes it possible to explain the challenges and possibilities for resizing of pedagogical practices.